Effect of ultrasound on protoscoleces of Echinococcus granulosus in vitro and in vivo - Asmaa A. Ali; Baraa B. Ramadhan (Iraqi Journal of Veterinary Sciences, 2021)
The current study was designed to investigate the effect of ultrasound on the protoscoleces of Echinococcus granulosus by enforcing steady numeral of frequencies during a certain interval (20000 pulse/s) (1.8 w/cm2), using exposure time 30,20,15,12,10 and 5s, individually and respectively. Consequently, six albino mice groups were immunized against cystic echinococcosis, which injected with exposed protoscoleces, to acquire specific cell-mediated immunity, called delayed type-hypersensitivity (DTH) which assessment by measurement the foot pad density. The results displayed significant excess (P≤ 0.001) of DTH by increase of foot pad thickness in injected groups. The results showed maximum thickness of 1.54 mm, 1.4mm, 0.9 mm. after 3h, 24h, and 48h post - injection, respectively, that compared with the thickness of control group 1.072, 0.638, 0.328 mm, respectively, during five months of experiment. The present research exhibited the action of ultrasonication technique on the viability of Echinococcus granulosus protoscoleces in vitro. Conclusion, Ultrasound frequencies used in the present study could be have consequential impact on the cellular immunity in albino mice.